Assessment of postoperative pain after unilateral mastectomy using two different surgical techniques in dogs - Minto, Bruno W. [UNESP]; Rodrigues, Lisiane C. [UNESP]; Steagall, Paulo V. M. [UNESP]; Monteiro, Eduardo R. [UNESP]; Brandao, Claudia V. S. [UNESP] (Biomed Central Ltd., 2013)
Background: There are few studies reporting pain and postoperative analgesia associated with mastectomy in dogs. The aim of this study was to evaluate postoperative pain after unilateral mastectomy using two different surgical techniques in the dog.Findings: Twenty female dogs were assigned (n=10/group) to undergo unilateral mastectomy using either the combination of sharp and blunt dissection (SBD) or the modified SBD (mSBD) technique, in which the mammary chain is separated from the abdominal wall entirely by blunt (hand and finger) dissection except for a small area cranial to the first gland, in a prospective, randomized, clinical trial. All dogs were premedicated with intramuscular acepromazine (0.05 mg/kg) and morphine (0.3 mg/kg). Anesthesia was induced with intravenous ketamine (5 mg/kg) and diazepam (0.25 mg/kg), and maintained with isoflurane. Subcutaneous meloxicam (0.2 mg/kg) was administered before surgery. Postoperative pain was evaluated according to the University of Melbourne pain scale (UMPS) by an observer who was blinded to the surgical technique.. Rescue analgesia was provided by the administration of intramuscular morphine (0.5 mg/kg) if pain scores were > 14 according to the UMPS. Data were analyzed using t-tests and ANOVA (P>0.05). There were no significant differences between the groups for age, weight, extubation time, and duration of surgery and anesthesia (P>0.05). There were no significant differences for postoperative pain scores between groups. Rescue analgesia was required in one dog in each group.Conclusions: The two surgical techniques produced similar surgical times, incidence of perioperative complications and postoperative pain. Multimodal analgesia is recommended for treatment of postoperative pain in dogs undergoing unilateral mastectomy.
Keywords: Dog; Cancer; mastectomy; analgesia; Surgery